2012
DOI: 10.1159/000339529
|View full text |Cite
|
Sign up to set email alerts
|

Kinesin Expression in the Central Nervous System of Humans and Transgenic hSOD1G93A<b> </b>Mice with Amyotrophic Lateral Sclerosis

Abstract: Background: Amyotrophic lateral sclerosis is a fatal motor neuron degenerative disease. Most cases are sporadic (SALS), and approximately 10% are familial (FALS) among which over 20% are linked to the SOD1 mutation. Both SALS and FALS have been associated with retrograde axonal transport defects. Kinesins (KIFs) are motor proteins involved mainly in anterograde transport; however, some also participate in retrograde transport. Objective: The purpose of the study was to investigate and compare the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
(54 reference statements)
4
20
0
Order By: Relevance
“…KIFC3 is ubiquitously expressed, but its expression differs largely among tissues, e.g. it is high in epithelial cells of renal distal tubule but very low in the secretory epithelial cells of the small intestine, pancreas and various regions of the CNS [37,46]. Our present study indicates that it is also very low in PBMCs (approx.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…KIFC3 is ubiquitously expressed, but its expression differs largely among tissues, e.g. it is high in epithelial cells of renal distal tubule but very low in the secretory epithelial cells of the small intestine, pancreas and various regions of the CNS [37,46]. Our present study indicates that it is also very low in PBMCs (approx.…”
Section: Discussionmentioning
confidence: 55%
“…Many papers indicated that disorders in the intracellular transport might be crucial for the initiation or progression of motor neuron degeneration [35,41,42,43,44]. In our previous studies, we observed important changes in the expression of tau isoforms, kinesins and dynactin in various regions of the CNS obtained from autopsies of SALS patients and transgenic mice with symptoms of motor neuron degeneration [36,37,38,45]. In the present work we investigated the expression of motor proteins in PBMCs obtained from a cohort of Polish SALS patients in comparison with healthy blood donors, and patients with other neurological diseases such as atypical parkinsonism and ALS-mimicking disorders.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations